Potential compensatory mechanism for cognitive impairment in type 2 diabetes and prediabetes: altered structure-function coupling - Lu, Weiye; Huang, Xuan; Shen, Die; Wang, Kun; Wang, Jiahe; Diao, Ziyu; Qiu, Shijun (Frontiers in Endocrinology, 2025)
BackgroundStructure-function (SC-FC) coupling may be more sensitive to detecting changes in the brain than any single modality. The aim of this study was to investigate the effects of SC-FC coupling changes on cognition and their interactions in patients with prediabetes and type 2 diabetes mellitus (T2DM).MethodsA total of 493 participants (119 with normal glucose metabolism (NGM), 125 with prediabetes, and 249 with T2DM) were included in the study. Diffusion-weighted MRI and resting state functional MRI data were used to quantify SC-FC coupling. General linear model and linear regression analysis were used to evaluate the relationship between glucose metabolism, SC-FC coupling, and cognition. Mediation models were used to evaluate the mediating role of regional SC-FC coupling between diabetes-related measures and cognition.ResultsThe regional coupling strength of SC-FC varied greatly in different brain regions, but was strongest in the ventral attention and somatmotor network areas. Compared with NGM patients, T2DM patients had higher SC-FC coupling in the default mode network but lower SC-FC coupling in the limbic network. In addition, fasting glucose and HbA1c were associated with weaker SC-FC coupling in the limbic network, fasting insulin with higher SC-FC coupling in the limbic network, and HbA1c with higher SC-FC coupling in the dorsal attention network. Furthermore, through mediated models we found that SC-FC coupling in the limbic network suppressed the association between diabetes-related measures and cognition.ConclusionT2DM and diabetes-related measures were associated with abnormal SC-FC coupling of the limbic network. The recombination of SC-FC coupling relationships in the limbic network may indicate a potential compensatory mechanism for cognitive decline that begins in prediabetes.